2011
DOI: 10.1002/dvdy.22548
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic expression of two thrombospondins during axolotl limb regeneration

Abstract: The molecular processes underlying regeneration remain largely unknown. Several potential factors have been elucidated by focusing on the regenerative function of genes originally identified in a developmental context. A complementary approach is to consider the roles of factors involved in wound healing. Here we focus on the Thrombospondins, a family of secreted extracellular matrix proteins that have been implicated in skin wound healing in mammals. We show that a subset of Thrombospondins are expressed at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Depending upon orientation, T7 or Sp6 polymerase was used to transcribe the probe. In situ hybridization was performed as in (Whited et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Depending upon orientation, T7 or Sp6 polymerase was used to transcribe the probe. In situ hybridization was performed as in (Whited et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…This expression intensifies as the blastema cells proliferate over the next 2 wk. However, once differentiation commences within the regenerate, tsp-4 expression becomes restricted to the perichondrium around the developing cartilage, consistent with, for instance, a role in the branching of the skeletal elements (32). We cloned the axolotl tsp-4 ORF downstream of our CA mini -O1O2O3 promoter/ operator sequence (termed pO-Tsp4) and coinjected newly fertilized axolotl eggs with pO-Tsp4 and pCAG-LacI to generate mosaic F 0 cotransgenic axolotls.…”
Section: Testing the Ability Of Various Inducible Genetic Systems To mentioning
confidence: 94%
“…Previously, we had found that two genes encoding axolotl thrombospondins, thrombospondin-1 (tsp-1) and thrombospondin-4 (tsp-4), displayed dynamic expression patterns in discrete cell types during the course of limb regeneration (32). Although thrombospondins have been implicated in numerous aspects of mammalian biology (33), including some that may be pertinent to regeneration such as wound healing and angiogenesis, nothing is known about their potential role in appendage regeneration.…”
Section: Testing the Ability Of Various Inducible Genetic Systems To mentioning
confidence: 99%
“…Limbs were processed as described previously (Whited et al, 2011). Cryosections were rehydrated in PBS, blocked in PBS/2% BSA/0.1% Triton for 30 minutes, incubated in primary antibody (chicken anti-GFP, 1:1000, Abcam), washed three times in PBS for 5 minutes and incubated in secondary antibody (donkey anti-chick or goat anti-chick, AlexaFluor 488-conjugated, 1:250, Jackson Labs).…”
Section: Histologymentioning
confidence: 99%
“…Animals were bred in-house or obtained from the Ambystoma Genetic Stock Center (AGSC) (Lexington, KY) and were between 6 and 12 cm long and size-matched within experiments, except where noted. Amputations were performed as described previously (Whited et al, 2011).…”
Section: Animalsmentioning
confidence: 99%